Analysing the Presence of Enslaved Black People in Ancient Java Society - Siti Maziyah (Diponegoro University, 2022)
Since the 7th century, Java has been one of the trading centres of Southeast Asia. It is recorded in an inscription in Java which contains several terms that indicate the presence of foreigners in old Javanese society, including enslaved Black people. The research questions posed include: Who are they? How did they get to Java? What was their role in Javanese society? The data used for this research are inscriptions, Chinese news sources, and contemporary literary texts. Its information was analysed and classified to determine its origin and presence in Java. The results showed that there were several enslaved Black people in Java. Based on the term used to describe them, they came from East Africa and Papua. Implicitly, the brief information shows that the existence of enslaved Black people in Java was linked to the trade conducted by Persians and people from East Indonesia. It shows that work in Java from the 7th century AD to the 15th century AD was performed with various nations. The king used the existence of enslaved Black people in Java as a way to gain spiritual